Estupro de vulnerável: um estudo de caso, quando o direito é mais danoso que o crime? - Silva, Jéssica Naiara Aquino da (Universidade Federal Rural do Semi-Árido, 2017)
This work seeks to analyze the concrete application of criminal law. State Public Defense from Rio Grande do Norte/Mossoró Nucleus received the work case, object of the actual research. This is about a relationship of a 35 (thirty-five) year old man with an 13 (thirteen) year old girl at the time of dating, which it didn’t have connivance and approval from her family. The related man was denunciated and went through in the sanctions of art. 217-A (rape of vulnerable) combined with art. 71, both of the Brazilian Penal Code. At the end of the criminal investigation, the judge acquitted the accused because he had consolidated a new family relationship with the young woman and had conceived a daughter. The current research objectifies to demonstrate the said device is outdated in its entirety through the social adequacy, by typify that the under 14 (fourteen) years old individual is sexually vulnerable. Nowadays, one must to review the vulnerability fixed in the analyzed device cautiously, singly, case by case, considered in such a way to avoid objectifications and injustices, specifically with regard to the concept of vulnerable being
Artigo Acadêmico
Keywords: Estupro de vulnerável; Vulnerabilidade; Adequação social; Intervenção mínima; CIENCIAS SOCIAIS APLICADAS::DIREITO